Phytoplankton communities and water quality in the Nhue - Day river system - Thuy, Duong Thi; Nguyet, Vu Thi; Cuong, Ho Tu; Phuong Quynh, Le Thi (Academia Journal of Biology, 2012)
The Nhue-Day river system is a good example of peri-urban river which is strongly influenced by the human activites in the whole basin (basin area: 7949 km2). Recently, the water quality and biodiversity of this river system has been reduced due to receiving the wastewater from point and non-point sources in its basin. In this paper, the actual status of water environment quality and the variation of phytoplankton community structure have been investigated, in terms of species composition in the Nhue-Day river system. The monthly sampling surveys were organized during the period 2007 - 2008 at 5 sites along the Day river and at the Khe Tang in the Nhue river. In terms of water quality, the physico-chemical variables such as water temperature, pH, dissolved oxygen, turbidity, nitrate-nitrogen, nitrite-nitrogen, ammonia-nitrogen, total phosphorus, silica and Chl a were analyzed. The results showed that the water quality tended to decrease from the upstream to the downstream of river system, notably in the Day river section after receiving the Nhue river or receiving the industrial and domestic wastewater. During this period, the phytoplankton community investigation showed that a total of 170 phytoplankton species belonging Bacilariophyceae, Euglenophyceae, Chlorophyceae, Dinophyceae and Cyanobacteria were observed. Aulacoseira, Cyclotella, Fragilaria, Pediastrum, Staurastrum species were abundant in upstream and whereas Euglena, Phacus, Oscillatoria, Spirulina, Merismopedia, Microcystis, Lyngbya were clearly dominant in the polluted sites (downstream) of the Nhue - Day river system. The cell number of phytoplankton species varied much in both temporal and spatial ways, especially in the rainy season. Our results clearly revealed the close relationship between water quality, in terms of physico-chemical variables and the phytoplankton community structure, in terms of species composition in the Nhue-Day river system. The results of this study opened the posibility of utilization of phytoplankton community structure as bioindicator for assessing the water quality in Vietnam.